2021
DOI: 10.1158/1055-9965.epi-20-1690
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Testosterone, Sex Hormone Binding Globulin and Colorectal Cancer Risk: Observational and Mendelian Randomization Analyses

Abstract: BackgroundEpidemiological studies evaluating associations between sex steroid hormones and colorectal cancer risk have yielded inconsistent results. To elucidate the role of circulating levels of testosterone, and sex hormone-binding globulin (SHBG) in colorectal cancer risk we conducted observational and Mendelian randomization (MR) analyses. MethodsThe observational analyses included 333,530 participants enrolled in the UK Biobank with testosterone and SHBG measured. Hazard ratios (HRs) and 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Previously, in the WHI-CT, we found a more than 2-fold higher colorectal cancer risk when the highest and lowest quartiles of SHBG were compared ( 12 ). In contrast, results from our current analysis of postmenopausal European women found no association between SHBG concentrations and colon cancer risk, consistent with results from US, UK, and Japan-based studies ( 10 , 14 , 36 ) as well as a recent Mendelian randomization study ( 37 ). Overall, these results do not support a causal role for SHBG in colorectal cancer development and suggest that the previously reported associations were likely biased (eg, through confounding) or were the result of chance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previously, in the WHI-CT, we found a more than 2-fold higher colorectal cancer risk when the highest and lowest quartiles of SHBG were compared ( 12 ). In contrast, results from our current analysis of postmenopausal European women found no association between SHBG concentrations and colon cancer risk, consistent with results from US, UK, and Japan-based studies ( 10 , 14 , 36 ) as well as a recent Mendelian randomization study ( 37 ). Overall, these results do not support a causal role for SHBG in colorectal cancer development and suggest that the previously reported associations were likely biased (eg, through confounding) or were the result of chance.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted, however, that this study used a less sensitive assay to measure sex hormone concentrations, and more than 60% of the participants had measured testosterone concentrations below the LLOQ ( 14 ). In the current analysis of postmenopausal European women, similar to studies of UK and US women ( 8 , 36 ) and a recent Mendelian randomization study ( 37 ), we found no association between circulating testosterone levels and colon cancer risk. We also found no association between circulating concentrations of androstenedione and DHEA with colon cancer risk.…”
Section: Discussionsupporting
confidence: 85%
“…Estrogen has been shown not only to enhance immunological markers and response, but also to be linked to T-cell proliferation, which might be involved in the immune response to the infection of SARS-CoV-2 ( Taneja, 2018 ). Most hormone (about 60%) is tightly bound to sex hormone-binding globulin (SHBG), which is an important regulator of the bioactivities of estrogens and testosterone ( Raverot et al, 2010 ; Dimou et al, 2021 ). In addition, sex hormone signaling could also regulate the insulin-like growth factor (IGF-1) concentrations, which were also reported to be associated with acute respiratory distress syndrome ( Ahasic et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…(7) Most hormone (about 60%) is tightly bound to sex hormone-binding globulin (SHBG), which is an important regulator of the bioactivities of estrogens and testosterone. (8,9) In addition, sex hormone signaling could also regulate the insulin-like growth factor (IGF-1) concentrations, which were also reported to be associated with acute respiratory distress syndrome. (10) It is therefore hypothesized that sex hormone and its related biomarkers might contribute to the sex difference of COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%